Female Sexuality in Aotearoa/New Zealand: Factors and Sexual Response Associated with Masturbation. Issue 4 (2nd October 2022) - Csako, Rita I.; Rowland, David L.; Hevesi, Kriszta; Vitalis, Emese; Balalla, Shivanthi
Abstract: Objectives: Sexual health includes the state of physical, emotional, mental, and social well-being related to sexuality. Masturbation is an important sexual activity with many potential benefits which has gained considerable interest in sexuality research in the past twenty years; however, this research is the first of its kind within the Aotearoa/New Zealand context. In this in-depth investigation, we examined frequencies of, reasons for, and activities during masturbation as well as the relationship between masturbation and other factors. Methods: Participants were 698 New Zealand women at least 18 years of age participating in a 42-item anonymous online survey collecting comprehensive information about sexual practices and related factors. Results: The results indicated that female masturbation has high prevalence in the New Zealand population. Conclusion: The pattern of results enabled us to identify the positive effects of masturbation, masturbation practices commonly used by New Zealand women and the differences between New Zealand women who masturbate frequently and less frequently.